Elimination of Interfacial Lattice Mismatch and Detrimental Reaction by Self‐Assembled Layer Dual‐Passivation for Efficient and Stable Inverted Perovskite Solar Cells - Zhang, Jiaqi; Yang, Jia; Dai, Runying; Sheng, Wangping; Su, Yang; Zhong, Yang; Li, Xiang; Tan, Licheng; Chen, Yiwang (Advanced energy materials, 2022)
Interfacial lattice mismatch and adverse reaction are the key issues hindering the development of nickel oxide (NiOx)‐based inverted perovskite solar cells (PVSCs). Herein, a p‐chlorobenzenesulfonic acid (CBSA) self‐assembled small‐molecule (SASM) is adopted to anchor NiOx and perovskite crystals to endow dual‐passivation. The chlorine terminal of SASMs can provide growth sites for perovskite, leading to interfacial strain release. Meanwhile, the sulfonic acid group from SASMs can passivate surface defects of NiOx, conducive to charge carrier extraction. In addition, the self‐assembled layer inhibits the adverse interfacial reaction by preventing NiOx contact with perovskite. Therefore, the NiOx/CBSA‐based PVSCs obtain a champion power conversion efficiency (PCE) of 21.8%. Of particular note, the unencapsulated devices can retain above 80% of their initial PCE values after storage in a nitrogen atmosphere for 3000 h, in air with a relative humidity of 50–70% for 1000 h, and heating at 85 °C for 800 h, respectively. A p‐chlorobenzenesulfonic acid (CBSA)‐based self‐assembled layer dual‐passivation strategy is employed to effectively eliminate interfacial lattice mismatch and detrimental reactions in NiOx‐based perovskite solar cells, which achieves unencapsulated devices preserving above 80% of initial efficiencies after storing in N2 for 3000 h, in air with a relative humidity of 50–70% for 1000 h, and heating at 85 °C for 800 h, respectively.